Plant population differentiation and climate change: responses of grassland species along an elevational gradient. (26th December 2013) - Frei, Esther R.; Ghazoul, Jaboury; Matter, Philippe; Heggli, Martin; Pluess, Andrea R.
Abstract Mountain ecosystems are particularly susceptible to climate change. Characterizing intraspecific variation of alpine plants along elevational gradients is crucial for estimating their vulnerability to predicted changes. Environmental conditions vary with elevation, which might influence plastic responses and affect selection pressures that lead to local adaptation. Thus, local adaptation and phenotypic plasticity among low and high elevation plant populations in response to climate, soil and other factors associated with elevational gradients might underlie different responses of these populations to climate warming. Using a transplant experiment along an elevational gradient, we investigated reproductive phenology, growth and reproduction of the nutrient‐poor grassland species Ranunculus bulbosus, Trifolium montanum and Briza media. Seeds were collected from low and high elevation source populations across the Swiss Alps and grown in nine common gardens at three different elevations with two different soil depths. Despite genetic differentiation in some traits, the results revealed no indication of local adaptation to the elevation of population origin. Reproductive phenology was advanced at lower elevation in low and high elevation populations of all three species. Growth and reproduction of T. montanum and B. media were hardly affected by garden elevation and soil depth. In R. bulbosus, however, growth decreased and reproductive investment increased at higher elevation. Furthermore, soil depth influenced growth and reproduction of low elevation R. bulbosus populations. We found no evidence for local adaptation to elevation of origin and hardly any differences in the responses of low and high elevation populations. However, the consistent advanced reproductive phenology observed in all three species shows that they have the potential to plastically respond to environmental variation. We conclude that populations might not be forced to migrate to higher elevations as a consequence of climate warming, as plasticity will buffer the detrimental effects of climate change in the three investigated nutrient‐poor grassland species.